Deployment of olive-stone waste as a substitute growing medium component for Brassica seedling production in nurseries - Chrysargyris, Antonios; Antoniou, Omiros; Athinodorou, Filio; Vassiliou, Rea; Papadaki, Anastasia; Tzortzakis, Nikos G. (My University, 2019)
In the Mediterranean region, olive-stone waste (OSW) is accumulated and considered of environmental and human health constraints. In this study, OSW was used for peat (P) replacement in growing media for Brassica seedling production. Cauliflower, broccoli, and cabbage were seeded in growing media consisted of 0-20-40-60% OSW. The mixture of OSW with peat increased growing media bulk density and reduced the total pore space and available water and air at root system. A Considerable amount of minerals were provided into the growing media with the OSW, while their availability was increased with the raised pH values. Seed emergence percentage decreased with high ratio of OSW which also increased mean emergence time. The addition of OSW decreased plant height, leaf number, and fresh weight in all three examined species. The OSW decreased stomatal conductance (in cauliflower and cabbage) and chlorophylls content (including broccoli). The insertion of OSW affected the mineral accumulation in plants with decreases in nitrogen and sodium content and increases in potassium and calcium. OSW increased to some extent for cauliflower and broccoli or unchanged for cabbage polyphenolic content and antioxidant activity (ABTS, FRAP). Cellular damage was caused by the addition of OSW by increasing the lipid peroxidation and the production of hydrogen peroxide, and as a consequence, the plant antioxidative (catalase, superoxide dismutase) enzyme metabolism increased. The current study demonstrates that up to 20% of OSW can substitute peat for cauliflower, broccoli, and cabbage seedling production while cabbage was performed better under the increased OSW-caused stress.
Keywords: Antioxidants; Germination; Growth; Olea europaea; Olive-stone waste; Peat; Vegetables